Effective length of bamboo-like stiffened hollow cylindrical structures. (2nd June 2022) - Nishiyama, Ryo; Sato, Motohiro
ABSTRACT: Hollow cylindrical structures are susceptible to local buckling because they flatten and significantly reduce their stiffness when they bend. Therefore, many previous studies aimed to improve the strength of pipelines and building structures were conducted. Our research group has focused on bamboo and has theoretically proven that stiffness anisotropy caused by bamboo's unique nodes and vascular bundles enhances the stiffness of cylindrical structures. In this study, to investigate this analytically, we carried out a finite-element analysis and succeeded in deriving a new dimensionless parameter that the stiffening effect of an anisotropic consideration. This result is applicable to a wide range of cylindrical structures, from thin-walled to thick-walled, and it is expected that bamboo-inspired bionic designs will be proposed in the future.